Teacher Professional Development Through Neuroeducation: A Hybrid Learning Approach to Brain-Based Teaching Competence - Baso Intang Sappaile; Palesa Molefe; KabelaD Dube; Dineo Modise (Yayasan Adra Karima Hubbi, 2025)
Background. Recent advances in neuroscience have opened new pathways for enhancing educational practices, particularly through the integration of brain-based principles into teaching. However, many educators remain underprepared to translate neuroeducational knowledge into classroom strategies, highlighting a gap in professional development frameworks. Purpose. This study aims to design, implement, and evaluate a hybrid learning model for teacher professional development that enhances brain-based teaching competence through neuroeducation. Using a mixed-method approach, the research engaged 72 in-service teachers across three institutions in a 10-week hybrid training program combining asynchronous modules, interactive webinars, and reflective practice. Method. Quantitative data from pre- and post-tests revealed a statistically significant increase in participants’ knowledge and application of neuroeducational principles (p < 0.001). Qualitative data from journals and interviews indicated improved instructional planning, learner engagement, and classroom adaptability. Results. The findings suggest that a hybrid model rooted in neuroeducation can effectively foster pedagogical transformation by bridging neuroscience and educational practice. Conclusions. This study offers a scalable and evidence-informed framework for equipping educators with brain-based competencies necessary for 21st-century learning environments.